Single-Stage Bidirectional Triple Active Bridge AC-DC converter for Single Phase Grid Applications - Hernandez M.A. (2020)
The design of a Single-Stage Three Port AC-DC converter is analyzed in this article. The structure analyzed is the Triple Active Bridge (TAB) single phase AC-DC converter which can be used for charging of Plug in Hybrid Electric Vehicles or to control the power flow in a micro-grid composed by a renewable source, a battery pack and the single phase grid. The analysis of the converter is focused in the modulation and the high frequency (HF) transformer sizing. The three winding transformer allows safety and voltage matching between the three sources. The sources are connected to the HF transformer with three active bridges which are modulated with a fixed frequency. To compensate the time-variant AC grid voltage in the HF transformer, the grid voltage is modulated with a 50% duty ratio and, the renewable DC source and the battery are modulated with a low frequency sinusoidal time-variant duty ratio. The turn ratio relationship of the HF transformer is chosen to assure inner mode modulation. Bidirectional power flow is controlled by phase shift modulation. This modulation strategy allows soft switching in all active bridges leading to higher efficiency of the converter. The simulation of a 1-KW topology confirms the advantages of the proposed methodology. © 2020 IEEE.